Calculating three-dimensional fluid flow in the spiral casing of the reversible hydraulic machine in turbine mode - Drankovskiy, Viktor Eduardovich; Rezvaya, Kseniya Sergeevna; Krupa, Evgeniy Sergeevich (НТУ "ХПИ", 2016)
One of the stages of a numerical research of water passage of the reversible hydraulic machine in turbine mode was described with program packages. Graphical results in the form of the velocity and pressure distributions in the predetermined modes of operation of reversible hydraulic machine were obtained. On the basis of these data can beobtained average kinematic parameters of the flow, which are determined in the inlet of calculation domain. Analysis of this numerical research was performed.

Описан один из этапов проведения численного исследования проточной части обратимой гидравлической машины в турбинном режиме с использованием пакетов программ. Получены графические результаты в виде полей распределения скоростей и давлений в заданных режимах работы обратимой гидравлической машины. На основании этих данных могут быть получены осредненные кинематические параметры потока, которые определены в расчетной области подводящей части. Проведен анализ данного численного исследования.
Расчет трехмерного потока жидкости в спиральной камере обратимой гидромашины в турбинном режиме
Keywords: numerical research; water passage; stay vanes; calculated mode; pressure distribution; численное исследование; подводящая часть; проточная часть; колонны статора